Changes in seagrass carbon stock: implications of decreasing area and percentage cover of seagrass beds in Barranglompo Island, Spermonde archipelago, South Sulawesi, Indonesia. Issue 1 (May 2021) - Mashoreng, S; Nafie, Y A La; Selamat, B; Isyrini, R; Amri, K
Abstract: Seagrass ecosystems in shallow waters, including in highly dense small islands, are vulnerable to anthropogenic activities and may lead to a decreasing in seagrass area and percentage cover. As a result, it will negatively affect climate change mitigation, i.e. a decrease in seagrass carbon stock. This research was conducted to evaluate seagrass carbon stock changes in Barranglompo Island, Spermonde archipelago, in 2001 and 2017. Carbon stock estimation was carried out by collecting seagrass biomass based on the category of a sparse, medium, and dense seagrass coverage (each with 20 replications) and analysing their carbon concentrations. Changes in carbon sequestration were analysed using an estimated approach to the changes in the seagrass bed areas. Landsat and Worldview-2 image analysis were utilized to estimate the area of seagrass beds in 2001 and 2017, respectively. Results showed a decrease in seagrass beds by 9.9 ha, from 66.8 ha in 2001 to 56.9 ha in 2017, or an average of 0.62 ha per year. Based on that, it was estimated that seagrass carbon stocks had declined from 74.19 tons in 2001 to 65.21 tons in 2017 or decreased by an average of 0.75% per year. Anthropogenic activities, such as boat anchors as well as household waste disposal in the seagrass area, are considered having the potential in causing a decrease in seagrass area and the percentage coverage.